(untitled) (Research, Society and Development, 2022)
This article aims to investigate the contributions that Art can promote in the process of implementing an inclusive school. It addresses the existing relations between Art and Inclusion precisely because this theme is of great importance in the educational context. The research in question seeks to explain the contributions that knowledge related to Art can promote in the process of transforming an excluding school into a truly inclusive school. The study is based on Bibliographic Review or Systematic Literature Review, based on materials published in scientific journals and institutional websites, as well as books and articles in order to obtain qualitative data, since these data aim to address the subjective aspects of social phenomena and human behavior.